Couple enjoying a musical concert in a grove - Temples of India Project Team (Jio Institute, 2024)
Couples invoking shringara rasa (associated with romance, love and attractiveness between lovers) are framed in panels with pillars and tiered shikhara with gavaksha (horseshoe) motifs. The face of the female figure is missing and the face of the male figure is defaced. They are wearing heavy jewellery, elaborate headgear, and garments, indicating they are a royal couple. The central male figure and female figures are enjoying a musical concert in a grove. They are seated on raised circular seats, and the male is seated in the lalitasana pose. The female figure is leaning towards the male and playing a stringed musical instrument (likely a veena). They are surrounded by four smaller figures. A male soldier is holding a sword and shield (on the left). One musician is playing the flute (bottom), sitting between the seats. A small female attendant (top right) is whispering in the ear of the central female. Mangoes are hanging from the tree branches.